Misuse of Topical Corticosteroids in Dermatological Disorders in Tribhuvan University Teaching Hospital - Chudal, Diwakar; Paudel, Vikash (Journal of Nepal Health Research Council, 2021)
Background: Topical corticosteroids are one of the most commonly used drugs in dermatology. Their improper use lead to serious adverse effects. However, it’s commonly misused by patients and chemists in Nepal. The main objective of the study was to determine the pattern of misuse of topical corticosteroids, its adverse effects, and factors associated with its misuse. Methods: This was a hospital-based, descriptive study conducted in a tertiary center of Nepal for three months. Patients meeting the inclusion criteria were enrolled in this study. Purposive sampling technique was used. Ethical approval was taken prior to study. Informed consent was taken from patients and interviewed using semi-structured questionnaire. The data was analyzed using Microsoft Excel and SPSS software. Results: Two hundred sixteen patients comprised the study population where males (54.5%) outnumbered females. The mean age was 28.72 years with 21-30 years as the most frequent range. Beclomethasone dipropionate (27.3 %) and clobetasol propionate (26.9%) were the most commonly misused drugs. The most common purposes for the application of these drugs were fungal infections (66%), pigmentary disorders (15%), such as fairness cream, acne, etc. Over-the-counter sale of topical corticosteroids (62%) was significantly higher than other forms of prescription. Aggravation of fungal infections (61.6%), acneiform erruptions, striae, and steroid induced dermatoses were common adverse effects. Conclusions: Topical corticosteroids are common misused drug with high over the counter sales. It is advised that drug authority should take necessary actions for its unethical use. Besides, awareness programs should be conducted for its rational use in public. Keywords: Dermatological disorders; misuse; over the counter drugs; steroids; topical corticosteroids